Estudo da colmatação em um pavimento de concreto permeável moldado in loco - Furtado, Leonardo (2023)
Urbanization is a consequence of the construction of houses, paved streets, sidewalks and various impermeable constructions on the ground, which cause a greater runoff of rainwater. To solve or mitigate this problem, permeable pavements are used, whose objective is the infiltration of rainwater through a permeable surface, being directed to a reservoir of stones that serves as the base for the pavement. The formation of clogging in permeable pavements is the main cause of their loss of drainage efficiency. Clogging occurs when particles and debris build up in the pores of the material. A factor influencing clogging is the age of the pavement, causing a decrease in the infiltration rate over the years. When permeable pavements are laid out in the rain, there is a tendency for waste carried by rainwater to clog the pores and reduce the rate of water infiltration. On the other hand, the granulometry of the aggregates also influences clogging. The aim of this study was to determine the influence of clogging on drainage efficiency in a permeable concrete pavement over time, as well as to observe the effect of implementing preventive maintenance on clogging. The place where the experiments were carried out was on the campus of the Federal University of Santa Maria (UFSM) in Frederico Westphalen-RS. The permeable concrete pavement was executed in loco, with circulation of pedestrians and light vehicles. The test carried out in the present study, to verify compliance with the standard and to monitor the collating process, followed the method described in Annex A of ABNT NBR 16416 (2015). In all, 27 tests were carried out at three points, between September 2021 and September 2022, with an interval of approximately 15 days between them, making up all seasons of the year. Three maintenance works were carried out on the pavement. Points 1, 2 and 3, which were monitored over a year, showed, through their parameters of hydraulic conductivity, porosity and infiltration rate, a significant effect caused by clogging of the pavement. These parameters had a drastic reduction, with emphasis on Points 1 and 2, which presented lower absolute values in relation to Point 3. Maintenance was more effective for Point 6, and Points 4 and 5 presented a more accentuated clogging, therefore, the recovery of hydraulic conductivity was not as efficient through maintenance. In future studies, it is recommended that a longer monitoring period would be able to further explore the characteristics and behavior of the clogging process in permeable pavement.